2019
DOI: 10.3390/jintelligence7010007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student’s Achievement Gaps between Ethnic Groups in Brazil

Abstract: Achievement gaps refer to the difference in the performance on assessments of students belonging to different social groups. Achievement gaps between ethnic groups have been observed in countries with heterogeneous populations. In this paper, achievement gaps between ethnic populations in Brazil were analyzed by studying the performance of a large cohort of senior high-school students in a standardized national exam. Ethnic groups were stratified by Brazilian states and socio-economic variables to homogeneize … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The research shows that ethnic has a significant effect on students' achievement. The research by Rocha & Nascimento (2019) revealed that the achievement gaps between ethnic groups have been observed in countries with heterogeneous populations.…”
Section: Discussionmentioning
confidence: 99%
“…The research shows that ethnic has a significant effect on students' achievement. The research by Rocha & Nascimento (2019) revealed that the achievement gaps between ethnic groups have been observed in countries with heterogeneous populations.…”
Section: Discussionmentioning
confidence: 99%